Oxidative stress and rheology in severe malaria. - Dondorp, A; Omodeo-Salè, F; Chotivanich, K; Taramelli, D; White, N (2003)
There is mounting evidence that the release of haemozoin (beta-haematin), which is produced in large amounts during malaria infection and is released into the circulation during schizont rupture, is associated with damage to cell membranes through an oxidative mechanism. The red blood cell membrane is thus oxidised, causing rigidity of the cell. This can contribute to the pathophysiology of severe malaria, since red blood cells will have to deform considerably in order to squeeze through the microcirculation, the patency of which is disturbed by sequestered red blood cells containing the mature forms of the parasite. Rigidity of red blood cells forms a new target for intervention. Since this seems to be caused by oxidative damage to the red blood cell membrane, the anti-oxidant N-acetylcysteine is a promising candidate for adjunctive treatment in severe malaria, which still has a mortality rate as high as 20%.